2019
DOI: 10.7150/ijms.34749
|View full text |Cite
|
Sign up to set email alerts
|

The phenotype of vascular smooth muscle cells co-cultured with endothelial cells is modulated by PDGFR-β/IQGAP1 signaling in LPS-induced intravascular injury

Abstract: Background Sepsis, a leading cause of death in intensive care units, is generally associated with vascular dysfunction. However, its pathophysiological process has not been fully clarified, lacking in-depth knowledge of its pathophysiological process may hinder the improvement of diagnosis and therapy for sepsis. Hence, as the key parts of the vascular wall, the interaction between endothelial cells (ECs) and smooth muscle cells (SMCs) under septic situation need to be further studied.Methods ECs and SMCs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…It has been reported that CTEPH endothelial cells can exhibit pro-fibrotic and pro-inflammatory phenotypes, as demonstrated by the expression of genes (COL1A1 and COL3A1) involved in extracellular matrix production and fibril organization [20]. In addition, PDGF is a potent mitogen for cells of mesenchymal origin, such as fibroblasts and smooth muscle cells [21]. Previous studies have revealed that smooth muscle 22 (SM22) and α-smooth muscle actin (α-SMA) are major marker genes of smooth muscle cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that CTEPH endothelial cells can exhibit pro-fibrotic and pro-inflammatory phenotypes, as demonstrated by the expression of genes (COL1A1 and COL3A1) involved in extracellular matrix production and fibril organization [20]. In addition, PDGF is a potent mitogen for cells of mesenchymal origin, such as fibroblasts and smooth muscle cells [21]. Previous studies have revealed that smooth muscle 22 (SM22) and α-smooth muscle actin (α-SMA) are major marker genes of smooth muscle cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…The SMC-EC co-culturing systems have been recently applied in the investigation of cardiovascular diseases 18 , 19 . Zheng et al found that the phenotype of vascular SMCs co-cultured with endothelial cells is modulated by platelet-derived growth factor receptor beta/IQ motif containing GTPase activating protein 1 signaling in lipopolysaccharides-induced intravascular injury 20 . In the aspect of preeclampsia studies, Dunk et al developed an in vitro co-culture system in which first trimester villous explants are cultured at low oxygen tension in contact with 2-mm 2 sections of decidua parietalis from the same patient 21 .…”
Section: Discussionmentioning
confidence: 99%